Targeting Multiple Signal Transduction Pathways of Sars‐Cov‐2: Approaches to Covid‐19 Therapeutic Candidates - Echeverria-Morgado, J (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Due to the complicated pathogenic pathways of coronavirus disease 2019 (COVID‐19), related medicinal therapies have remained a clinical challenge. COVID‐19 highlights the urgent need to develop mechanistic pathogenic pathways and effective agents for preventing/treating future epidemics. As a result, the destructive pathways of COVID‐19 are in the line with clinical symptoms induced by severe acute coronary syndrome (SARS), including lung failure and pneumonia. Accordingly, revealing the exact signaling pathways, including inflammation, oxidative stress, apoptosis, and autophagy, as well as relative representative mediators such as tumor necrosis fac-tor‐α (TNF‐α), nuclear factor erythroid 2‐related factor 2 (Nrf2), Bax/caspases, and Beclin/LC3, re-spectively, will pave the road for combating COVID‐19. Prevailing host factors and multiple steps of SARS‐CoV‐2 attachment/entry, replication, and assembly/release would be hopeful strategies against COVID‐19. This is a comprehensive review of the destructive signaling pathways and host– pathogen interaction of SARS‐CoV‐2, as well as related therapeutic targets and treatment strategies, including potential natural products‐based candidates. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.